Measurement of aggression in older adults. (March 2021) - Ravyts, Scott G.; Perez, Elliottnell; Donovan, Emily K.; Soto, Pablo; Dzierzewski, Joseph M.
Abstract: Aggressive behaviors are prevalent in late-life and are associated with important consequences for older adults, caregivers, and healthcare providers. Age-related changes in the manifestation of aggression are precipitated in part by the rise of cognitive impairment. Such changes necessitate the use of psychometrically sound measures. The present article identifies existing measures of aggression for older adults, highlights the strengths and limitations of these measures, and proposes avenues for future research in this area. Five full-scale measures of aggression, as well as five subscales of aggression embedded within larger non-aggression measures in older adults were identified. Overall, measures of aggression specific to late-life are predominately observational and limited to individuals with dementia or older adults living in long-term care settings. The psychometric properties of aggression scales in late-life generally indicate adequate internal consistency, interrater reliability, and concurrent validity. In contrast, the reliability and validity of subscales of aggression contained within larger neuropsychiatric measures are more difficult to ascertain due to limited research. Future investigations would benefit from examining the psychometric properties of widely-used self-report measures of aggression among older adults, further evaluating the psychometric properties of aggression subscales, and developing additional measures which are predictive of aggressive behaviors. Highlights: Measures vary with respect to aspects of aggression assessed, source of information, and time period covered. Existing measures are mostly observational and focus on older adults with dementia or those in long-term care facilities. Though limited psychometrics exists, most scales demonstrate adequate consistency, reliability, and validity. The reliability and validity of self-report measures of aggression among older adults remain understudied.